Autophagy deficiency promotes triple-negative breast cancer resistance to T cell-mediated cytotoxicity by blocking tenascin-C degradation - Li, Zhi-Ling; Zhang, Hai-Liang; Huang, Yun; Huang, Jun-Hao; Sun, Peng; Zhou, Ning-Ning; Chen, Yu-Hong; Mai, Jia; Wang, Yan; Yu, Yan; Zhou, Li-Huan; Li, Xuan; et al. (Nature communications, 2020)
Most triple-negative breast cancer (TNBC) patients fail to respond to T cell-mediated immunotherapies. Unfortunately, the molecular determinants are still poorly understood. Breast cancer is the disease genetically linked to a deficiency in autophagy. Here, we show that autophagy defects in TNBC cells inhibit T cell-mediated tumour killing in vitro and in vivo. Mechanistically, we identify Tenascin-C as a candidate for autophagy deficiency-mediated immunosuppression, in which Tenascin-C is Lys63-ubiquitinated by Skp2, particularly at Lys942 and Lys1882, thus promoting its recognition by p62 and leading to its selective autophagic degradation. High Tenascin-C expression is associated with poor prognosis and inversely correlated with LC3B expression and CD8 + T cells in TNBC patients. More importantly, inhibition of Tenascin-C in autophagy-impaired TNBC cells sensitizes T cell-mediated tumour killing and improves antitumour effects of single anti-PD1/PDL1 therapy. Our results provide a potential strategy for targeting TNBC with the combination of Tenascin-C blockade and immune checkpoint inhibitors. T cell mediated therapies have proven largely unsuccessful in triple-negative breast cancer (TNBC). Here, the authors show that autophagy is reduced in TNBC, which results in an increase in Tenascin C and reduced activation of tumour infiltrating lymphocytes.